2019
DOI: 10.1097/mao.0000000000002252
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Posterior Canal Benign Paroxysmal Positional Vertigo Tends to Reoccur

Abstract: Objective: We analyzed the clinical characteristics of quite a large cohort of patients with bilateral posterior canal benign paroxysmal positional vertigo (bil-BPPV) with respect to the rate and types of recurrence. Study Design: Retrospective case review. Setting: Outpatient dizziness clinic. Patients: About 2,050 patients diagnosed with BPPV during the years 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In human patients with acute vestibular syndrome, the underlying causes are typically divided into isolated or recurrent conditions. Relapse of vestibular neuritis is rare (1.9%) but benign paroxysmal positional vertigo, Ménière's disease and vestibular migraine will often recur with an approximate prevalence of 30-50%, 45-79% and up to 81% respectively [31][32][33]. It seems likely that dogs diagnosed with IVS may in fact have more than one underlying cause for these signs, therefore explaining the different presentations (mostly related to acute or chronic onset, progression or not of clinical signs and concurrent facial nerve deficits or not), MRI findings (enhancement or not of cranial nerves VII and/or VIII), outcome and recurrence of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…In human patients with acute vestibular syndrome, the underlying causes are typically divided into isolated or recurrent conditions. Relapse of vestibular neuritis is rare (1.9%) but benign paroxysmal positional vertigo, Ménière's disease and vestibular migraine will often recur with an approximate prevalence of 30-50%, 45-79% and up to 81% respectively [31][32][33]. It seems likely that dogs diagnosed with IVS may in fact have more than one underlying cause for these signs, therefore explaining the different presentations (mostly related to acute or chronic onset, progression or not of clinical signs and concurrent facial nerve deficits or not), MRI findings (enhancement or not of cranial nerves VII and/or VIII), outcome and recurrence of clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Pollak and Michael have reported that the incidence of bilateral posterior canal BPPV is 6.9 per cent of all cases of posterior canal BPPV. 11 However, Imai et al have reported that bilateral posterior canal BPPV accounted for 1.4 per cent of cases, 4 and Hotta et al reported a 2.2 per cent incidence. 3 The incidence of true and pseudo bilateral posterior canal BPPV in this study was 3.1 per cent and 12.6 per cent, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Recurrence of clinical signs in dogs with IVS is reported in approximately one‐quarter of cases (Orlandi et al, 2020). In human patients, relapse is also commonly seen with vestibular neuritis, benign paroxysmal positional vertigo, Ménière's disease and vestibular migraine (Fushiki et al, 2009; Maione, 2006; Pollak & Michael, 2019). No recurrence was observed in any of the cases in this study.…”
Section: Discussionmentioning
confidence: 99%